Enhancing Religious Tourism Through Sea Transportation: A Transnational Approach to Batam and Singapore - Celerina Dewi Hartati; Danny Faturachman; Yulie Neila Chandra; Gustini Wijayanti (Khazanah Sosial, 2025)
Batam City, which is part of the Riau Islands Province, serves as a connecting hub between Indonesia and Singapore. Batam is strategically located in a border area between countries, neighboring one of the world's business centers, Singapore. Therefore, maritime transportation plays a crucial role in a maritime nation like Indonesia. The high intensity of transportation between Batam and Singapore indicates that both cities are tourist destinations. Residents of both Batam and Singapore view these cities as tourist destinations. This study focuses on religious tourism. The high intensity of maritime transportation is particularly evident during weekends and holiday seasons, as many residents of both cities visit each other's locations, which shows the high intensity of social mobilization. This study aims to highlight maritime aspects and their relationship with society through the concept of transnationalism within the framework of tourism, particularly religious tourism. With globalization and the need to expand networks, maritime transportation is essential to support transnational processes. For this reason, maritime safety is vital, as it significantly influences efforts toward sustainable development, especially in maritime transportation activities that support tourism.